The Soul as a Cord: The Role of the Ethical-Kabbalistic Image in Formulating Compassionate Awe in Liqqutei amarim and Nefesh haḥayyim. - Sachs-Shmueli, Leore (Prooftexts, 2026)
According to the image of the cord, originating in modern moral literature, the human soul is like a cord dangling from God into the human body. Human actions shake the cord from the bottom up, strengthen and weaken it, and may even cut it. This image, common in many Hasidic writings, emphasizes the deep bond between the human soul and God and the danger inherent in the flaw of sin. In this article, I will focus on how Rabbi Shneur Zalman of Liadi (1745–1812) adapted this image. I will argue that it served to inspire his readers with a combined feeling of an "uncanny compassion," allowing us to broaden our exploration of awe and include a new dimension: its relation to compassion. In addition, I will go outside the Hasidic circle and examine the similarities and differences in the adoption of the image in Rabbi Ḥayyim of Volozhin's discourse of awe in the book Nefesh haḥayyim. The comparison will facilitate an appreciation of the common modern, nineteenth-century, Eastern European kabbalistic formulations of fear of sin, as well as discern and recognize Hasidic attitudes toward sin.1